The pharmacokinetic profile of brensocatib and its effect on pharmacodynamic biomarkers including NE, PR3, and CatG in various rodent species - Basso, Jessica; Chen, Kuan-Ju; Zhou, Yuchen; Mark, Lilly; LaSala, Daniel; Dorfman, Arielle; Atalla, Mary; Chun, Donald; Viramontes, Veronica; Chang, Christina; Leifer, Franziska; McDonald, Patrick P.; et al. (Frontiers in Pharmacology, 2023)
Brensocatib is a novel, oral, selective, reversible inhibitor of dipeptidyl peptidase 1 (DPP1), which activates several neutrophil serine proteases (NSPs), including neutrophil elastase (NE), proteinase 3 (PR3), and cathepsin G (CatG) in the bone marrow during the early stage of neutrophil maturation. These NSPs are associated with pathogen destruction and inflammatory mediation; their dysregulated activation can result in excess secretion of active NSPs causing damaging inflammation and contributing to neutrophil-mediated inflammatory and autoimmune diseases. Pharmacological inhibition of DPP1 in the bone marrow could therefore represent an attractive strategy for these neutrophil-driven diseases. A completed Phase 2 trial in non-cystic fibrosis bronchiectasis patients (ClinicalTrials.gov number NCT03218917; EudraCT number: 2017-002533-32) indeed demonstrated that administration of brensocatib attenuated the damaging effects of chronic inflammation by inhibiting the downstream activation of NSPs. To support a range of preclinical programs and further understand how rodent species and strains may affect brensocatib's pharmacokinetic (PK) profile and its pharmacodynamic (PD) effects on NE, PR3, and CatG, an extensive naïve dosing study with brensocatib at different dosing levels, frequencies, and durations was undertaken. Dose-dependent PK exposure responses (AUC and Cmax) were observed regardless of the rodent species and strain. Overall, mice showed greater reduction in NSP activities compared to rats. Both mice and rats dosed once daily (QD) had equivalent NSP activity reduction compared to BID (twice a day) dosing when the QD dose was 1.5-times the BID daily dose. For both mouse strains, CatG activity was reduced the most, followed by NE, then PR3; whereas, for both rat strains, PR3 activity was reduced the most, followed by CatG, and then NE. Maximum reduction in NSP activities was observed after ∼7 days and recoveries were nearly symmetrical. These results may facilitate future in vivo brensocatib study dosing considerations, such as the timing of prophylactic or therapeutic administration, choice of species, dosage and dosing frequency.